Dechema chemistry data series : vapor liquid equilibrium data collection 2e Organic hydroxy compounds, alcohols (supplement 3) - Gmehling, J.; Onken, U.; Rarey-Nies, J. R. (Frankfurt Dechema, 1988)
part 2e
Keywords: Vapor-Liquid equilibrium; Binary mixtures -- Data tables and diagrams; Organic hydroxy compounds